Peer-to-peer accommodation prices: city listing concentration and host listing share. - Bárcena-Martín, Elena María; Benítez-Aurioles, Beatriz; Pérez-Moreno, Salvador Jesús (SAGE, 2023)
This article examines the relationship of city listing concentration and host listing share with prices in the peer-to-peer accommodation market. To this end, a multilevel analysis is applied to data from 216,960 Airbnb listings in 45 cities. The results reveal that while city-level concentration does not significantly affect prices, the listing share of each supplier does have a significant effect. This highlights that host listing shares can explain the ability of agents to influence the price of their accommodations even in relatively competitive markets such as peer-to-peer accommodation. Our findings have theoretical implications relating to the idiosyncratic aspects that affect business pricing, as well as practical implications in the private sphere for the rest of the hospitality and tourism industry, and for public policy in terms of regulations.
Política de acceso abierto tomada de: https://www.sherpa.ac.uk/id/publication/13304
Keywords: Gentrificación; Alojamientos turísticos; Política de vivienda; Peer-to-peer accommodation; Airbnb; Prices; Concentration; Listing share